A SAÚDE E A NUTRIÇÃO NA ESCOLA: UMA ANÁLISE DA TRIAGEM SOBRE A VIDA SAUDÁVEL NO COTIDIANO E ESCOLAR NO CEPI-SERGIO FAYAD GENEROSO DO ENSINO MÉDIO NO MUNICÍPIO DE FORMOSA GOIÁS - Martins da Silva, Maysa (LINKSCIENCEPLACE, 2026)
In an educational context where healthy living is often the ultimate teaching tool used by schools throughout Brazil, this work aims to analyze how the School Screening of Formosa Goiás CEPI addresses the issue of Nutrition in School. The promotion has over the last few years performing as a promising strategy in the field of Public Health in Schools. Therefore, this study aimed to verify how's School Everyday Health as its theme. The methodology was made a preliminary screening to check the progress of school health in the CEPI - Sergio Fayad Generoso of Formosa Goiás State Education Network, an analysis of the screening was made later, verifying aspects such as: Blood Pressure, Blood Sugar, Weight and Height. The results show that screening applied to the network using the slope defending human responsibility for public health, with a superficial approach, but diversified with various graphics, supplementary texts and activities proposed, is intended to link the issue of health and nutrition in the contemporary debate health promotion, analyzing screening in this process. Against the recognition of the complexity of health framework / Brazilian food arising from the healthy transition underway in the country, the proposed health promotion highlights perspectives but also challenges to the field of health and nutrition. Generally speaking, new demands in academic training and care model tend to foster a search for partnerships, innovation in eating practices nutritional education aimed at the achievement of nutritional citizenship.